Metabolic abnormalities in patients treated with percutaneous nephrolithotomy. (November 2015) - Nandwani, GM; Stoves, J; Azhar, MF; Pereni, CI; Shah, T
Objectives: To assess metabolic abnormalities in patients with percutaneous nephrolithotomy (PCNL) that could pose a risk for stone recurrence. Materials and methods: The data was collected retrospectively on all patients who had PCNL and metabolic studies, between January 2000 and September 2012. Results: There were 144 patients; median age and follow up were 49.5 (15– 4) years and 80.2 (16–180) months, respectively. Nearly half of the patients had staghorn calculus. Metabolic abnormalities (MAs) were found in 55 (38.2%). The 31 (21.5%) of these had multiple metabolic abnormalities (MMA) while 24 (16.6%) had a single metabolic abnormality (SMA). Uricosuria was found in 24 (16.6%), hyperoxaluria in 22 (15.3%), hyperphosphaturia in 18 (12.5%), hypercalciuria in 10 (7%), hypomagnesuria in 6 (4.2%), cystinuria in 5 (3.5%) and hypocitraturia in 5 (3.5%). Hyperuricaemia was present in 10 (7%), hypercalcaemia in 5 (3.5%), hyperphosphataemia in 7 (5%) and renal tubular acidosis in 1 (0.7%). In non-staghorn, MAs were found in 25 (35.2%) and 16 (64%) of these had MMA. In patients with staghorn, MAs were present in 30 (41%) patients. Half of the patients 15 (50%) in this group had MMA. A high proportion of the first time stone formers requiring surgical treatment had MAs and 57% of these had MMA. Stone analysis was available for 69 (48%) and 37 (53.6%) of these had mixed composition. The highest proportion of patients with uric acid stones had MA 89% followed by cystine stones 80%, matrix stones 50%, calcium oxalate 36.6%, carbonate apatite 36.4% and triple phosphate 33.3% . Conclusion: A high proportion of first time stone formers, staghorn and non-staghorn stone formers with PCNL had MA. These findings suggest that the treatment of metabolic abnormalities can play an important role in reducing the risk of stone recurrences and management may include referral to dedicated metabolic stone clinics.